Preparation method and application of high-performance lithium-sulfur battery positive composite electrode new material S / CuCo2S4 / CNTs
Through the combination of electrospinning and hydrothermal method, S/CuCo2S4/CNTs nanofiber composite materials were prepared, which solved the problem of insufficient structural stability and electrochemical performance of MWCNTs in the positive electrode materials of lithium sulfur batteries, and achieved higher electrical Chemical properties and structural stability.
Patent Information
- Application Number
- CN202411379817.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-02-11
AI Technical Summary
Existing lithium-sulfur battery positive electrode materials have shortcomings in electrochemical performance and structural stability, especially the structural parameters of multi-walled carbon nanotubes (MWCNTs) in the production process, resulting in the actual conductivity being lower than theoretical expectations and high Surface energy can easily cause agglomeration and uneven dispersion.
Electrospinning technology is used to uniformly load MWCNTs on the nanofiber framework, and doped Cu and Co bimetals by hydrothermal method to prepare S/CuCo2S4/CNTs nanofiber composite materials to enhance structural stability and electrochemical properties.
Through the combination of electrospinning and hydrothermal method, the structural stability and electrochemical performance of MWCNTs are significantly improved, the ion/electronic conductivity is enhanced, and the electrochemical performance of lithium-sulfur batteries is improved.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrocatalytic materials, and in particular to a preparation method and application of a new high-performance lithium-sulfur battery positive composite electrode material S / CuCo2S4 / CNTs. Background Art
[0002] With the rapid growth of domestic new energy vehicle production capacity, the demand for higher performance electrode materials continues to grow with the rapid development of the new energy field. Although the specific capacity of lithium-ion batteries is close to the theoretical limit, it is still difficult to meet the market's growing demand for higher capacity batteries. In this context, people have turned their attention to high energy density electrode materials and new lithium secondary battery systems, such as lithium-sulfur batteries.
[0003] Traditional lithium-ion batteries store energy through lithium-ion intercalation, while lithium-sulfur batteries are based on the LiPSs conversion reaction of multi-electron transfer at the solid-liquid interface. This mechanism gives lithium-sulfur batteries a high theoretical specific capacity, but they also face many application challenges due to complex multi-electron and multi-phase reactions. In order to overcome the problems that hinder the development of lithium-sulfur batteries, researchers have proposed a variety of improvement strategies. Its positive electrode, as an active material loading electrode, has advantages in reducing costs and simplifying processes. The preparation of positive electrode materials by combining elemental sulfur with modified carriers is a popular technical research at present. According to the type of carrier, it can be divided into carbon / sulfur, polymer / sulfur and metal compound / sulfur composites.
[0004] Studies have shown that carbon-based materials, as the main body of the positive electrode of lithium-sulfur batteries, can inhibit volume expansion, conduct electrons, and allow the electrolyte to fully wet the positive electrode. It is the preferred positive electrode material for lithium-sulfur batteries to anchor lithium polysulfide through strong adsorption with sulfur and reduce the shuttle effect. Nazar et al. pioneered the fixation of sulfur in the regular structure of CMK-3, achieving a high reversible specific capacity and high stability of 1320mAh g-1. Since then, research on carbon / sulfur composite materials has gradually increased. Lou et al. innovatively designed a double-layer hollow carbon sphere structure to confine sulfur and successfully synthesized a new type of carbon / sulfur composite material. This structure not only shows flexibility, but also effectively encapsulates sulfur and inhibits the diffusion of polysulfides into the electrolyte. Archer et al. successfully synthesized hollow mesoporous carbon spheres as an efficient carrier of sulfur using a template method, with a sulfur loading of up to 70wt%. Yang et al. used Cu-MOF as a template to successfully prepare 1D oriented ordered cross-linked hierarchical porous carbon fibers (CHPCFs), which provide storage space for ions and sulfur while providing Li +Transport provides a fast channel. Lei et al. successfully developed a NiCo2S4@C modified functional diaphragm material using metal organic frameworks, which showed good inhibition of lithium ion diffusion. In 1991, Japanese scientist Iijima used high-resolution electron microscopy to carefully observe arc evaporation graphite products, revealing a new type of nanoscale carbon crystals-carbon nanotubes (CNTs). The addition of CNTs has made a great contribution to the improvement of the sulfur storage performance of composite materials. Wang et al. proposed a 3D membrane in which multi-walled carbon nanotubes (MWCNTs) can be used as interactive nanofillers without short circuits even when the content reaches 2.5wt% due to negligible electronic conductivity. Although MWCNTs are widely used as supporting materials in the field of electrochemistry due to their excellent mechanical strength, huge specific surface area, excellent conductivity and electrochemical stability. However, the current production process of MWCNTs has serious defects, resulting in uneven product structure parameters and actual conductivity far lower than theoretical expectations. In addition, high surface energy can easily induce agglomeration in electrochemical reactions, which not only hinders the uniform dispersion of MWCNTs in the polymer matrix but also affects the structural stability.
[0005] However, there is still a lack of detailed experimental design and research on different metal-doped MWCNTs composite electrode materials. Therefore, how to improve the structural stability of MWCNTs and improve their electrochemical properties, so that carbon nanotubes can show better electrochemical and mechanical properties and significantly improve the performance of lithium-sulfur batteries has become one of the current research hotspots. Single-component transition metal sulfides have limitations as electrodes, such as poor conductivity, irreversible capacity loss and volume expansion. To overcome these shortcomings, can we provide a preparation method and performance control strategy for metal-doped MWCNTs to construct composite electrode materials? We will focus on the preparation method, structural characterization and electrochemical performance evaluation of metal-doped MWCNTs; establish the relationship between preparation process, components, structure and electrochemical performance; explore the best preparation conditions by regulating the metal doping concentration and doping method, and obtain a multi-component new composite electrode material (as a positive sulfur-carrying material for lithium-sulfur batteries) by compounding different transition metal sulfides, which exhibits excellent electrochemical properties through mutual reinforcement or complementarity. In this way, a ternary composite material of carbon nanotubes and bimetallic sulfides is prepared, and the electrochemical performance is improved by using the advantages of multiple components, and the application potential of various metal-doped MWCNTs composite electrode materials in the field of energy storage and conversion is evaluated? However, there has been no public report so far. Summary of the invention
[0006] In view of the above situation, in order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a preparation method and application of a high-performance lithium-sulfur battery positive composite electrode new material S / CuCo2S4 / CNTs, MWCNTs (multi-walled carbon nanotubes) are uniformly loaded on a nanofiber skeleton by electrospinning, and then doped with Cu and Co bimetallics by hydrothermal method to prepare a composite electrode material S / CuCo2S4 / CNTs, which is assembled into a one-dimensional carbon material by electrospinning and hydrothermally loaded with heteroatoms to enhance the structural stability and electrochemical properties of MWCNTs, and at the same time, the effect of sulfur modification is utilized to further enhance the ionic / electronic conductivity, and it is used as a sulfur-loaded material for Li-S batteries to improve the electrochemical performance of the battery, comprising the following steps:
[0007] (1) Prepare the precursor solution
[0008] Place N,N-dimethylformamide (DMF) in a beaker, add polyacrylonitrile (PAN) powder, and stir in a magnetic stirrer at a constant temperature until it is completely dissolved to obtain a uniform light yellow viscous PAN / N,N-dimethylformamide precursor solution;
[0009] (2) Preparation of MWCNTs / PAN nanofiber solution
[0010] Considering that multi-walled carbon nanotubes (MWCNTs) are easy to agglomerate in solution due to their high surface energy, carboxylated MWCNTs were used as a reinforcing agent for acid treatment to improve their dispersibility in solution;
[0011] First, the precursor solution obtained in step (1) is weighed, and then the acidified MWCNTs are added, and the mixture is dispersed by magnetic stirring, and then the mixture is ultrasonically treated in an ultrasonic instrument, and then the mixture is continuously stirred on a magnetic stirrer until the solution becomes clear, thereby obtaining a MWCNTs / PAN nanofiber solution;
[0012] (3) Electrospinning PAN / MWCNTs nanofiber membrane
[0013] The MWCNTs / PAN nanofiber solution prepared in step (2) is injected into a syringe, and electrospinning is performed using a drum-type electrospinning device to obtain a PAN / MWCNTs nanofiber membrane, which is then placed in a drying oven and dried at a constant temperature to remove residual solvent and ensure the stability of the fiber structure;
[0014] (4) Preparation of S / CuCo2S4 / CNTs nanofiber composites
[0015] First, Cu(CH3COO)2·H2O (copper acetate monohydrate) and Co(CH3COO)2·4H2O (cobalt acetate tetrahydrate) are mixed, and then thiourea is added to obtain a Cu.Co.S mixture, which is dissolved in ethanol and stirred at room temperature by a magnetic stirrer to form a uniform and stable solution. Subsequently, the solution is mixed with a PAN / MWCNTs nanofiber membrane prepared by electrospinning, and the mixture is placed in an oven for heat preservation and reaction, and loose particles on the surface of the reactants are removed to obtain a CuCo2S4 / CNTs nanofiber composite material.
[0016] (5) Preparation of composite electrode material S / CuCo2S4 / CNTs
[0017] The CuCo2S4 / CNTs nanocomposite material prepared in step (4) is mixed and ground with sulfur in a weight ratio of 1:4, and under argon protection, the temperature is gradually increased to 160°C and kept warm for 12 hours. The granular CuCo2S4 formed during the heating process is gradually adsorbed onto the surface of the carbon fiber to obtain a composite electrode material S / CuCo2S4 / CNTs (i.e., bimetallic copper cobalt sulfide and carbon nanotube material).
[0018] The composite electrode material S / CuCo2S4 / CNTs prepared by this method is used in the preparation of high-performance lithium-sulfur battery positive electrodes.
[0019] The preparation method of the present invention is scientific and reasonable, easy to operate, and a multi-component novel composite electrode material (as a sulfur-carrying material for the positive electrode of a lithium-sulfur battery) is obtained by compounding bimetallic sulfides. A ternary composite material of carbon nanotubes and bimetallic sulfides is prepared by reinforcing or complementing each other's excellent electrochemical properties. The electrochemical properties are improved by utilizing the advantages of multiple components, and the application potential of various metal-doped MWCNTs composite electrode materials in the field of energy storage and conversion is expanded, which has significant economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The MWCNTs / PAN nanofiber preparation process of the present invention is
[0021] Figure 2 SEM images of MWCNTs / PAN nanofibers at different MWCNTs mass fractions of the present invention, (a) without purification, (b) 0.05wt%, (c) 0.1wt% and (d) 0.2wt%
[0022] Figure 3 TEM image of MWCNTs / PAN nanofibers of the present invention (MWCNTs mass fraction is 0.1wt%)
[0023] Figure 4 FT-IR spectra of MWCNTs / PAN nanofiber membranes containing different MWCNTs mass fractions of the present invention
[0024] Figure 5 This is the EDS surface scanning spectrum of CuCo2S4-2 / CNT of the present invention and its corresponding
[0025] Figure 6 (a) XPS full spectrum, (b) Co 2p, (c) Cu 2p and (d) S2p spectra of CuCo2S4-1 / CNTs nanofibers of the present invention
[0026] Figure 7 SEM images of (a) CuCo2S4-0.5 / CNT, (b) CuCo2S4-1 / CNT and (c) CuCo2S4-2 / CNT of the present invention
[0027] Figure 8 Electrochemical CV performance test of the present invention (a) CV curves of four materials, (b) CV curves of the first three cycles under the optimal ratio, (c) CV curves under improved sensitivity and (d) CV curves under reduced scanning speed
[0028] Fig. 9 Electrochemical EIS performance test of the present invention (illustration: equivalent circuit diagram)
[0029] Table 1 Experimental materials and specifications
[0030] Table 2 Experimental instruments and equipment DETAILED DESCRIPTION
[0031] The specific implementation methods of the present invention are described in detail below in conjunction with specific examples and specific circumstances.
[0032] The present invention can be shown in concrete facts by the following examples.
[0033] A method for preparing a high-performance lithium-sulfur battery positive electrode composite new material S / CuCo2S4 / CNTs, comprising the following steps:
[0034] (1) Prepare the precursor solution
[0035] 10 ml of N,N-dimethylformamide (DMF) was placed in a beaker, and polyacrylonitrile (PAN) powder was added to make a solution with a mass concentration of 12%. The mixture was stirred in a magnetic stirrer at a constant temperature of 60°C for 12 h until the mixture was completely dissolved, thereby obtaining a uniform light yellow viscous PAN / N,N-dimethylformamide solution, i.e., the precursor solution.
[0036] (2) Preparation of MWCNTs / PAN nanofiber solution
[0037] Considering that multi-walled carbon nanotubes (MWCNTs) are easy to agglomerate in solution due to their high surface energy, carboxylated MWCNTs were selected as a reinforcing agent for acid treatment to improve their dispersibility in solution;
[0038] First, the precursor solution obtained in step (1) was weighed, and 0.1% acidified MWCNTs were added, and magnetic stirring was performed for 1 hour for preliminary dispersion. To further improve the dispersion uniformity of MWCNTs, the solution was ultrasonically treated in an ultrasonic instrument for 2 hours, and then stirred on a magnetic stirrer for 6 hours until the solution was clear, thereby obtaining a MWCNTs / PAN nanofiber solution;
[0039] (3) Electrospinning PAN / MWCNTs nanofiber membrane
[0040] The MWCNTs / PAN nanofiber solution prepared in step (2) was injected into a 10 ml syringe using a drum-type electrospinning device. During the spinning process, the spinning flow rate was set to 0.6 ml h -1 , the receiving distance was 15 cm, the spinning voltage was controlled at 13±1 kV to ensure the stable jet of the spinning solution, and the PAN / MWCNTs nanofiber membrane was obtained by electrospinning. After the spinning was completed, the obtained PAN / MWCNTs nanofiber membrane was placed in a drying oven and dried at a constant temperature of 60°C for 12 h to remove the residual solvent and ensure the stability of the fiber structure;
[0041] (4) Preparation of S / CuCo2S4 / CNTs nanofiber composites
[0042] Weigh 1 mmol of Cu(CH3COO)2·H2O (copper acetate monohydrate) and 2 mmol of Co(CH3COO)2·4H2O (cobalt acetate tetrahydrate), mix and stir for 1 hour, then add 4 mmol of thiourea to obtain a Cu.Co.S mixture, dissolve it in 30 ml of ethanol, and stir it with a magnetic stirrer at room temperature to form a uniform and stable solution. Subsequently, mix the solution with the PAN / MWCNTs nanofiber membrane prepared by electrospinning, place it in a hydrothermal reactor, seal it, and then place it in an oven preset at 150°C for 12 hours of insulation reaction. The reactants are washed to remove loose particles on the surface, and the washed samples are placed in a 60°C oven again for low-temperature drying for 12 hours to ensure that the samples are fully dried to obtain CuCo2S4 / CNTs nanofiber composite materials.
[0043] (5) Preparation of composite electrode material S / CuCo2S4 / CNTs
[0044] The CuCo2S4 / CNTs nanocomposite material prepared in step (4) is mixed and ground with sulfur in a weight ratio of 1:4, and then heated to 160°C at a rate of 5°C / min under an argon atmosphere and kept warm for 12 hours. The granular CuCo2S4 formed in the hydrothermal process is gradually adsorbed onto the surface of the carbon fiber to obtain a composite electrode material S / CuCo2S4 / CNTs (i.e., bimetallic copper cobalt sulfide and carbon nanotube material).
[0045] The composite electrode material S / CuCo2S4 / CNTs prepared by this method is used in the preparation of high-performance lithium-sulfur battery positive electrodes.
[0046] The method of the present invention is scientifically and reasonably designed, easy to operate, and can be effectively used to prepare the composite electrode material S / CuCo2S4 / CNTs for preparing the positive electrode of high-performance lithium-sulfur batteries.
[0047] The preparation method and performance control strategy of metal-doped MWCNTs composite electrode materials will be studied, and the preparation method, structural characterization and electrochemical performance evaluation of metal-doped MWCNTs will be studied. The relationship between the preparation process, components, structure and electrochemical performance will be established, and the optimal preparation conditions will be explored by regulating the metal doping concentration and doping method. Therefore, the present invention uses electrostatic spinning to uniformly load MWCNTs on the nanofiber skeleton, and then combines the hydrothermal method to dope bimetallic (CuCo) to prepare a new type of nanofiber composite material S / CuCo2S4 / CNTs, that is, assemble into a one-dimensional carbon material by electrostatic spinning and hydrothermally load heteroatoms, thereby enhancing the structural stability and electrochemical performance of MWCNTs; at the same time, the effect of sulfur modification is used to further enhance the ion / electronic conductivity, and it is used for Li-S battery sulfur-carrying materials; finally, different transition metal sulfides are compounded to obtain a multi-component new type of composite electrode material (as a lithium-sulfur battery positive electrode sulfur-carrying material), which exhibits excellent electrochemical properties through mutual reinforcement or complementarity, thereby preparing a ternary composite material of carbon nanotubes and bimetallic sulfides. In short, CuCo2S4 / CNTs nanocomposite fiber materials of bimetallic sulfide and carbon nanotubes were synthesized by electrospinning combined with hydrothermal method; the optimal spinning parameters were explored by adjusting the concentration of the precursor solution; and then the loading amount of bimetallic sulfide CuCo2S4 nanoparticles was further changed to prepare a new multi-walled carbon nanotube-doped bimetallic cathode composite material S / CuCo2S4 / CNTs for high-performance lithium-sulfur batteries. After testing, the performance was stable and the service life was long. It is the crystallization of the applicant's creative labor. The relevant experimental data are as follows:
[0048] 1. Experimental raw materials and experimental instruments
[0049] The experimental raw materials and specifications are shown in Table 1, and the experimental instruments and equipment are shown in Table 2.
[0050] Table 1 Experimental materials and specifications
[0051]
[0052] Table 2 Experimental instruments and equipment
[0053]
[0054] 2. Design and Experiment of Technical Solution
[0055] The technical route of the experimental research is to synthesize CuCo2S4 / CNTs nanocomposite fiber materials of bimetallic sulfide and carbon nanotubes by electrospinning combined with hydrothermal method; explore the optimal spinning parameters by adjusting the concentration of the precursor solution; and then further change the loading amount of bimetallic sulfide CuCo2S4 nanoparticles. The specific scheme is:
[0056] (1) Prepare the precursor solution
[0057] Measure 10 ml of N,N-dimethylformamide and place it in a beaker. Weigh the PAN powder in proportion and add it to N,N-dimethylformamide at an average temperature of 60°C. Stir at a constant temperature for 12 hours under a constant temperature magnetic stirrer until it is completely dissolved to obtain a uniform light yellow mixed viscous solution (PAN / N,N-dimethylformamide solution). According to the preparation method, PAN spinning solutions with concentrations of 8%, 10%, 12%, and 14% can be obtained respectively.
[0058] (2) Optimizing and debugging the optimal process parameters for electrospinning
[0059] Use a syringe to extract about 5 ml of solution and squeeze out the bubbles in the solution. Place the syringe steadily on the electronic high voltage generator and ensure that it is placed horizontally. Firmly stick the aluminum foil on the receiving plate and accurately adjust its receiving distance from the syringe spinneret. After the spinning process starts, adjust the voltage intensity and solution flow rate until the spinning process reaches a stable and continuous state. After the spinning is completed, take out the fiber membrane and put it in a 60℃ oven to dry for 24 hours to fully volatilize the residual solvent inside the fiber membrane.
[0060] Pure PAN (polyacrylonitrile) N,N-dimethylformamide solution was used as the precursor of electrospinning fibers. The PAN electrospinning process and its influence on the final fiber morphology and regulation mechanism were optimized. Continuous PAN polymer nanofibers with small diameter and uniform distribution along the length of the fiber were obtained, and the corresponding optimal process parameters were as follows: PAN concentration was 12wt%, spinning voltage was 13kV, and flow rate was set to 0.6mL h -1 , the receiving distance is 15cm.
[0061] (3) Preparation of MWCNTs / PAN nanofibers
[0062] In view of the fact that multi-walled carbon nanotubes (MWCNTs) are easy to agglomerate in solution due to their high surface energy, carboxylated MWCNTs were selected as a reinforcing agent for acid treatment to improve their dispersibility in solution.
[0063] Figure 1 For the preparation process of MWCNTs / PAN nanofibers, first weigh an appropriate amount of N,N-dimethylformamide (DMF) and add a predetermined proportion (10%) of polyacrylonitrile (PAN) powder. Subsequently, stirring was continued for 12 hours at room temperature until a transparent and uniform PAN solution was obtained. Next, different proportions of acidified MWCNTs (0%, 0.05%, 0.1%, 0.2%) were added to the PAN solution, and magnetic stirring was performed for 1 hour for preliminary dispersion. In order to further improve the dispersion uniformity of MWCNTs, the mixed solution was placed in an ultrasonic instrument for ultrasonic treatment for 2 hours, and then continued to stir on a magnetic stirrer for 6 hours until the solution (PAN solution with different proportions of acidified MWCNTs added to form a solution) was clear.
[0064] This patent uses a drum-type electrospinning device to inject four solutions with different MWCNTs contents into a 10 ml syringe. During the spinning process, the spinning flow rate is set to 0.6 ml h -1 , the receiving distance was 15 cm, and the spinning voltage was controlled at (13±1) kV to ensure the stable jet of the spinning solution. Under the above conditions, PAN / MWCNTs nanofiber membrane was successfully prepared by electrospinning. After spinning, the obtained PAN / MWCNTs nanofiber membrane was placed in a drying oven and dried at a constant temperature of 60°C for 12 hours to remove residual solvent and ensure the stability of the fiber structure.
[0065] (4) Preparation of CuCo2S4 / CNTs nanofiber composites
[0066] Weigh 0.5mmol, 1mmol, 2mmol of Cu(CH3COO)2·H2O and 1mmol, 2mmol, 4mmol of Co(CH3COO)2·4H2O, respectively, mix and stir for 1h, then add 2mmol, 4mmol, 8mmol of thiourea, respectively, and dissolve in 30ml of ethanol after the weighing of the Cu.Co.S mixed solution. Stir with a magnetic stirrer at room temperature until a uniform and stable solution is formed. Subsequently, the solution is mixed with carbon nanofibers and transferred together to a 50ml hydrothermal reactor. After being completely sealed, it is placed in an oven preset at 150℃ and kept warm for 12h. After that, the reaction product is thoroughly cleaned to remove loose particles on the surface, and the cleaned sample is placed in a 60℃ oven again for low-temperature drying for 12 hours to ensure that the sample is fully dried. Named CuCo2S4-0.5 / CNTs, CuCo2S4-1 / CNTs, CuCo2S4-2 / CNTs nanofiber composites. Without adding acidified carbon nanotubes, other conditions were the same and a CuCo2S4-2 nanofiber composite material was obtained.
[0067] (5) Preparation of S / CuCo2S4 / CNTs nanofiber materials
[0068] The CuCo2S4 / CNTs nanocomposite material and sulfur were mixed and ground in a weight ratio of 1:4, and then heated to 160°C at a rate of 5°C / min under an argon atmosphere for 12 hours to obtain a S / CuCo2S4 / CNTs nanofiber composite material.
[0069] The ratio of CuCo2S4 particles loaded on CNTs nanofibers can be regulated by controlling the content of bimetallic sulfide. They are marked as CuCo2S4-0.5 / CNT, CuCo2S4 -1 / CNT and CuCo2S4-2 / CNT. The granular CuCo2S4 formed during the hydrothermal process gradually adsorbed onto the surface of carbon fibers.
[0070] 3. Morphology, structure and physical characterization
[0071] Through TEM analysis, MWCNTs have a high aspect ratio. Inside the nanofibers, MWCNTs are basically arranged parallel to the fiber axis, showing good orientation. At the same time, MWCNTs are effectively coated by the PAN matrix inside the nanofibers. Subsequent infrared spectroscopy (FT-IR) analysis further verified that the addition of MWCNTs did not destroy the group structure of the molecular chain of the PAN fiber itself, and the fiber molecular group remained stable under the addition of MWCNTs, as shown in the following details:
[0072] (1) Morphological analysis of MWCNTs / PAN nanofibers
[0073] from Figure 2 The results show that as the mass fraction of MWCNTs gradually increases from 0wt% to 0.05wt%, the surface of PAN / MWCNTs nanofibers is relatively smooth and the diameter changes slightly. In the range of MWCNTs mass fraction between 0.05wt% and 0.1wt%, MWCNTs can improve the fluidity of the spinning solution and the stretchability of the spinning jet. The viscosity and conductivity of the PAN / MWCNTs mixed solution increase, and the two present a dynamic equilibrium state, making the fiber diameter stable. However, when the mass fraction of MWCNTs exceeds 0.1wt%, the fiber diameter increases significantly and the diameter distribution becomes uneven. This phenomenon is mainly attributed to the excessive addition of MWCNTs, which significantly increases the viscosity of the spinning solution, making it difficult to stretch evenly, resulting in an increase in the fiber diameter; and because the solvent fails to completely evaporate, the fibers are prone to adhesion, which may cause unevenness.
[0074] (2) Distribution of MWCNTs in MWCNTs / PAN nanofibers
[0075] MWCNTs, with their significant aspect ratio, can be well oriented and arranged in a certain direction in the PAN fiber matrix, showing excellent orientation effects, such as Figure 3 As shown in Figure 2. This orientation effect is mainly attributed to the superior conductivity of MWCNTs themselves and the effective traction of the electric field force during electrospinning. In the nanofibers, MWCNTs are perfectly coated by PAN to form a "skin-core structure" to ensure the excellent performance of the nanofibers.
[0076] (3) Infrared analysis of MWCNTs / PAN nanofiber membrane
[0077] In order to further explore the specific effect of the addition of MWCNTs on the molecular structure of PAN nanofibers, this chapter conducted infrared spectroscopy (FT-IR) tests and analyses on MWCNTs / PAN nanofiber membranes containing different MWCNTs mass fractions. Figure 4 As shown in the figure, the test results show that the infrared spectra of MWCNTs / PAN nanofiber membranes with different MWCNTs mass fractions show a consistent change trend. This shows that the addition of MWCNTs does not change the basic structure of the PAN molecular group. This is mainly because MWCNTs are in a free state in the PAN fiber and do not form a new chemical bonding structure with the PAN molecule. It is only possible that the bond energy of the original chemical bond changes after coating due to the intermolecular force. This change is mainly manifested as adsorption, which is physical adsorption.
[0078] (4) Spinning heat treatment
[0079] In the preparation of carbon nanofibers, the pre-oxidation process significantly affects the structure and properties of the final carbon nanofibers. Specifically, PAN polymer fibers need to undergo a series of transformations, including pre-oxidation and subsequent calcination processes, to be converted into pre-oxidized fibers and finally obtain carbon nanofibers. According to the summary of existing studies and literature, in order to prepare these active materials, pure PAN fibers obtained by electrospinning technology and MWCNTs / PAN composite fibers with different MWCNTs contents were calcined under the protection of inert gas (nitrogen). First, the fibers were heated to 270°C at a heating rate of 2°C min-1 and kept at this temperature for 2h for pre-oxidation. Subsequently, by adjusting the heating rate to 5°C min-1, the fibers were further heated to 800°C and kept for 2h to complete the final calcination process, thereby obtaining the desired active materials. This calcination process ensures the stability of the fiber structure and the excellent properties of the final carbon nanofibers.
[0080] By combining the advanced technologies of electrospinning and hydrothermal method, a composite material (CuCo2S4 / CNTs nanofibers) of bimetallic sulfide CuCo2S4 nanoparticles loaded on carbon nanotubes with a unique structure was synthesized, the material morphology and structure were characterized, and the electrochemical properties were analyzed.
[0081] Characterization test of CuCo2S4 / CNTs carbon nanocomposites:
[0082] The ratio of CuCo2S4 particles loaded on CNTs nanofibers was regulated by controlling the content of bimetallic sulfide. They were labeled as CuCo2S4-0.5 / CNT, CuCo2S4-1 / CNT and CuCo2S4-2 / CNT. The granular CuCo2S4 formed during the hydrothermal process gradually adsorbed onto the carbon fiber surface.
[0083] In order to verify that CuCo2S4 particles have been loaded on carbon nanotubes, as Figure 5 (d) The material was subjected to elemental energy spectrum analysis. Figure 5 (ac) show the EDS image mapping of CuCo2S4-2 / CNTs nanofiber material, revealing the uniform presence of Cu, Co, and S elements, and it can be seen that CuCo2S4 particles are loaded on CNTs nanofibers.
[0084] In order to further verify that the loaded particles are CuCo2S4, XPS test is performed on the material. Figure 6 (a) In the full energy spectrum, Cu, Co, S, C, and O are detected. The appearance of the O peak may be due to the material absorbing oxygen from the atmosphere. Figure 6(b) is the XPS spectrum of Cu 2p. The peaks of Cu2p3 / 2 and Cu 2p1 / 2 correspond to about 951.68 eV and 931.78 eV, proving the existence of Cu2+. Figure 6 (c) is the XPS spectrum of Co2p, which can be fitted into six characteristic peaks; the peaks corresponding to Co 3+ are approximately 778.68eV and 796.38eV, and the peaks corresponding to Co 2+ are approximately 804.28eV and 780.08eV, accompanied by the presence of satellite peaks. Figure 6 (d) is the XPS spectrum of S2p. The peaks corresponding to S2- are approximately 163.28 eV and 162.08 eV, accompanied by the presence of satellite peaks, while the peak at 165.38 eV belongs to the bond between metal and S. The above confirms that CuCo2S4 has been successfully loaded on CNTs.
[0085] like Figure 7 (a)-(c) are SEM images of the three composite ratios. After heat treatment, the spun fibers still retain the morphology of the precursor. Figure 7 (a)-(b) It can be clearly seen that the loading amount of CuCo2S4 on CNTs is very small, which will reduce the active specific surface area of CNTs; Figure 7 (c) SEM image shows that CuCo2S4 particles are uniformly loaded on the surface of CNTs, and the particle content appropriately increases the catalytic active sites, which is expected to improve the electrochemical performance of lithium-sulfur batteries.
[0086] 4. Electrochemical performance experiment
[0087] (1) Electrochemical performance test
[0088] In order to further study the electrochemical properties of the composite material, this chapter conducted cyclic voltammetry and AC impedance tests on the material and analyzed the electrochemical activation area ECSA and impedance value Rct.
[0089] (2) Cyclic voltammetric characteristics
[0090] The electrochemical properties of CuCo2S4 / CNTs carbon nanocomposites were evaluated using a three-electrode system. Figure 8 (a) At a higher scan rate, the integrated area and current response of the CV curve of CuCo2S4-2 / CNTs are larger. Figure 8 (b) shows the CV curves of three scans. The second and third curves overlap highly, which indicates that this composite material has good cyclic reversibility. Figure 8(c)(d), when the sensitivity is increased and the scanning speed is reduced, the CV curve shows a redox peak. This is because the process is mainly a reversible redox reaction of Cu2+ / Cu3+ and Co2+ / Co3+. At the same time, when the scanning speed is reduced and the sensitivity is increased, the integral area of the curve increases and the shape hardly changes, all of which indicate that the synthesized material has good reversibility and stability.
[0091] (3) AC impedance performance analysis
[0092] In order to further reveal the effect of CuCo2S4 loading on electrochemical performance, EIS tests were conducted. The EIS curve consists of a semicircle in the high-frequency region and a slant line in the low-frequency region. The charge transfer resistance (Rt) is related to the semicircle in the high-frequency region of the EIS graph, and the low-frequency region is composed of lines with a certain slope. Generally speaking, the charge transfer resistance is related to the diameter of the semicircle, and increases with the increase in the diameter of the semicircle, and the lower the conductivity; the slope is related to the diffusion of ions. Fig. 9 As shown in the figure, compared with the sample without MWCNTs, the semicircle of the test with MWCNTs added is smaller, which indicates that MWCNTs are conducive to the transfer of ions, forming a better conductive network and improving the electrochemical performance. Comparing different addition amounts, the Rct of CuCo2S4-2 / CNTs is significantly smaller, and the slope of the oblique line is larger, indicating that the catalytic conversion ability is stronger under this ratio. Fig. 9 As shown in the illustration, after equivalent circuit fitting, the Rs values of CuCo2S4-2, CuCo2S4-0.5 / CNTs, CuCo2S4-1 / CNTs, and CuCo2S4-2 / CNTs nanofibers are 1.992Ω, 1.928Ω, 2.899Ω, and 1.855Ω, respectively; the Rs of the four composite materials are very small, indicating that the electrode material without binder can significantly reduce the inherent resistance of the material. At the same time, the Rct values of CuCo2S4-2, CuCo2S4-0.5 / CNTs, CuCo2S4-1 / CNTs, and CuCo2S4-2 / CNTs nanofibers are 3.167Ω, 4.19Ω, 2.893Ω, and 1.375Ω, respectively. This further confirms that CuCo2S4-2 / CNTs nanofibers have the best electrochemical performance.
[0093] In summary, by regulating the loading amount of CuCo2S4 particles on carbon nanotube nanofiber materials, the influence of the difference in the loading amount of CuCo2S4 nanoparticles on the morphology and structure of the composite material and the influence of different loading amounts of CuCo2S4 nanoparticles on the electrochemical performance of lithium-sulfur batteries were explored. It can be seen that CuCo2S4 nanoparticles are loaded on carbon nanotubes to obtain CuCo2S4 / CNTs nanofiber composite materials. Among them, the carbon nanotube material has a highly interconnected three-dimensional conductive network skeleton, which improves the overall conductivity of the CuCo2S4 / CNTs composite material. By optimizing the material design, efficient ion / electron transmission is achieved, and the electrochemical performance is significantly improved. At the same time, this design can withstand the repeated volume changes generated by the battery during the charge and discharge cycle. As an active component, bimetallic sulfide provides abundant chemical anchoring sites, effectively promotes the chemical adsorption of polysulfide, and thus significantly improves the conversion kinetics of polysulfide. The synergistic effect of this dual mechanism can effectively inhibit the shuttling behavior of polysulfide and enhance the cycle stability and service life of the battery.
[0094] It should be pointed out that the above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession can make changes or modify the technical contents disclosed above into equivalent embodiments with equivalent changes without departing from the scope of the technical solution of the present invention, which all fall within the protection scope of the present invention.
Claims
1. A high-performance lithium-sulfur battery positive electrode composite new material S / CuCo2S4 / CNTs and a preparation method thereof, characterized in that: The following steps are involved: (1) Prepare precursor solution Place N,N-dimethylformamide (DMF) in a beaker, add polyacrylonitrile (PAN) powder, and stir in a magnetic stirrer at a constant temperature until it is completely dissolved to obtain a uniform light yellow viscous PAN / N,N-dimethylformamide precursor solution; (2) Preparation of MWCNTs / PAN nanofiber solution Considering that multi-walled carbon nanotubes (MWCNTs) are easy to agglomerate in solution due to their high surface energy, carboxylated MWCNTs were used as a reinforcing agent for acid treatment to improve their dispersibility in solution; First, the precursor solution obtained in step (1) is weighed, and then acidified MWCNTs are added, dispersed by magnetic stirring, and then placed in an ultrasonic instrument for ultrasonic treatment, and then stirred on a magnetic stirrer until the solution becomes clear, thereby obtaining a MWCNTs / PAN nanofiber solution; (3) Electrospinning PAN / MWCNTs nanofiber membrane The MWCNTs / PAN nanofiber solution prepared in step (2) is injected into a syringe, and electrospinning is performed using a drum-type electrospinning device to obtain a PAN / MWCNTs nanofiber membrane, which is then placed in a drying oven and dried at a constant temperature to remove residual solvent and ensure the stability of the fiber structure; (4) Preparation of S / CuCo2S4 / CNTs nanofiber composites First, Cu(CH3COO)2·H2O (copper acetate monohydrate) and Co(CH3COO)2·4H2O (cobalt acetate tetrahydrate) are mixed, and then thiourea is added to obtain a Cu.Co.S mixture, which is dissolved in ethanol and stirred at room temperature by a magnetic stirrer to form a uniform and stable solution. Subsequently, the solution is mixed with the PAN / MWCNTs nanofiber membrane prepared by electrospinning, and the mixture is placed in an oven for heat preservation and reaction. The loose particles on the surface of the reactants are removed to obtain a CuCo2S4 / CNTs nanofiber composite material. (5) Preparation of composite electrode material S / CuCo2S4 / CNTs The CuCo2S4 / CNTs nanocomposite material prepared in step (4) was mixed and ground with sulfur in a weight ratio of 1:4, and the temperature was gradually increased to 160°C and kept for 12 h under argon protection. The granular CuCo2S4 formed during the heating process was gradually adsorbed onto the surface of the carbon fiber to obtain a composite electrode material S / CuCo2S4 / CNTs.
2. The method for preparing a high-performance lithium-sulfur battery positive electrode composite material S / CuCo2S4 / CNTs according to claim 1, characterized in that: The following steps are involved: (1) Prepare precursor solution Measure 10 ml of N,N-dimethylformamide (DMF) and place it in a beaker. Add polyacrylonitrile (PAN) powder to make a solution with a mass concentration of 12%. Stir in a magnetic stirrer at 60°C for 12 h until it is completely dissolved to obtain a uniform light yellow viscous PAN / N,N-dimethylformamide solution, i.e., the precursor solution. (2) Preparation of MWCNTs / PAN nanofiber solution Considering that multi-walled carbon nanotubes (MWCNTs) are easy to agglomerate in solution due to their high surface energy, carboxylated MWCNTs were selected as a reinforcing agent for acid treatment to improve their dispersibility in solution; First, the precursor solution obtained in step (1) was weighed, and 0.1% acidified MWCNTs were added, and magnetic stirring was performed for 1 h for preliminary dispersion. To further improve the dispersion uniformity of MWCNTs, the solution was ultrasonically treated in an ultrasonic instrument for 2 h, and then stirred on a magnetic stirrer for 6 h until the solution was clear, thereby obtaining a MWCNTs / PAN nanofiber solution; (3) Electrospinning PAN / MWCNTs nanofiber membrane The MWCNTs / PAN nanofiber solution prepared in step (2) was injected into a 10 ml syringe using a drum-type electrospinning device. During the spinning process, the spinning flow rate was set to 0.6 ml h -1 , the receiving distance was 15 cm, the spinning voltage was controlled at 13±1 kV to ensure the stable jet of the spinning solution, and the PAN / MWCNTs nanofiber membrane was obtained by electrospinning. After the spinning was completed, the obtained PAN / MWCNTs nanofiber membrane was placed in a drying oven and dried at a constant temperature of 60 °C for 12 h to remove the residual solvent and ensure the stability of the fiber structure; (4) Preparation of S / CuCo2S4 / CNTs nanofiber composites 1 mmol of Cu(CH3COO)2·H2O (copper acetate monohydrate) and 2 mmol of Co(CH3COO)2·4H2O (cobalt acetate tetrahydrate) were weighed, mixed and stirred for 1 h, and then 4 mmol of thiourea was added to obtain a Cu.Co.S mixture, which was dissolved in 30 ml of ethanol and stirred with a magnetic stirrer at room temperature to form a uniform and stable solution. Subsequently, the solution was mixed with the PAN / MWCNTs nanofiber membrane prepared by electrospinning, placed in a hydrothermal reactor, sealed, and then placed in an oven preset at 150 ℃ for 12 h of heat preservation reaction. The reactants were washed to remove loose particles on the surface, and the washed samples were placed in a 60 ℃ oven again for low-temperature drying for 12 hours to ensure that the samples were fully dried to obtain CuCo2S4 / CNTs nanofiber composite materials.
3. (5) Preparation of composite electrode material S / CuCo2S4 / CNTs The CuCo2S4 / CNTs nanocomposite material prepared in step (4) is mixed and ground with sulfur in a weight ratio of 1:4, and then heated to 160°C at a rate of 5°C / min under an argon atmosphere for 12 h. The granular CuCo2S4 formed in the hydrothermal process is gradually adsorbed onto the surface of the carbon fiber to obtain a composite electrode material S / CuCo2S4 / CNTs.
4. Application of the new composite electrode material S / CuCo2S4 / CNTs prepared according to any one of claims 1 to 2 in the positive electrode of a high-performance lithium-sulfur battery.
Citation Information
Cited By
Porous carbon composite material and preparation method thereof
CN120646831A